Perbandingan Hasil Eksperimen dan Numerik Kekuatan Lentur Balok Beton Bertulang dengan Bukaan (Opening) pada Kondisi Uncracked Section - Wijaya, Handika Setya; Supriyanti, Dipa (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
In the development of building design today, the aspect of efficiency is preferred. One example is in the construction of modern buildings, piping installation is needed to accommodate mechanical and electrical needs. One alternative plan to skip the piping installation is give an opening in the beam. The aim of this research is to find out how big the effect of giving a number of variations in the number of openings in the concrete compression zone to the strength and flexural strength of reinforced concrete beams. Tests carried out are flexural tests with beam test specimens measuring (15 x 25 x 200) cm. Variations of this study are the number of openings with a diameter of 5 cm, amounting to two openings (BB2) and four openings (BB4) and beams without openings (BK). From the results of the study showed that the provision of openings in the tensile zone of the concrete reduced the flexural strength although it was not significant. When compared with BK, the reduction of flexural strength for BB2 beams is 1.26% and the reduction for BB4 beams is 5.66%.